P302 Search for optimal protocol of temporal summation of experimental heat pain in healthy volunteers. Issue 3 (March 2017) - Moeller, N.; Hacker, H.; Hahnenkamp, K.; Usichenko, T.
Abstract : Question: Experimental human pain models are often insufficient to detect moderate effect of non-opioid analgesic drugs or hypoalgesic neuromodulation. Measurement of temporal summation of pain (TSP) is a promising tool for this purpose. The aim was to find out optimal stimulation parameters for a new protocol that consistently reproduces the TSP phenomenon. Material & methods: Twenty healthy volunteers (15 females) underwent 4 sessions with different stimulation parameters with an interval of at least 48 h in-between. After determining the individual pain threshold temperature, pulsating heat stimuli were applied to the left ventral forearm with a ramp rate of 20°C/s and a frequency of 0.33 Hz using a CHEPS thermode (Medoc, Israel). Stimulation temperature, pulse duration and number of stimuli were changed among the conditions I–IV ( Table 1). Participants rated the perceived pain of the first and every 10th heat stimulation using a numeric rating scale 0–100. TSP was calculated as the difference between the lowest rating and the rating of the last stimulus and was compared among 4 conditions. Results: Condition IV yielded the largest TSP effect (20 ± 3.1; mean ± SEM), which was higher than TSP effect of condition I (7.9 ± 2.2; p = 0.03) and II (6.8 ± 1.5; p = 0.012; Fig. 1). TSP effects of condition III and IV were comparable, however condition IV caused discomfort and intolerable pain in 9 participants; no one complained about discomfort during other conditions. Conclusion: The protocol with high number of repeated stimuli and short pulse duration (<1.0 s) is feasible to reproduce TSP phenomenon. Heat stimulation with long pulse durations and high stimulation temperatures are not feasible in experimental human pain research.